In vitro Cytotoxic and Anti-ROS Potentials of the Aerial Part of Pyrrosia lanceolata on A549 Cells and Cell Free Condition (Bangladesh Pharmaceutical Journal, 2024)
Antioxidants and cancer are somewhat related to each other. The study was designated to evaluate the antioxidant activities of the aerial parts of Pyrosia lanceolata (P. lanceilata, Fam. Polypodiaceae) and their cytotoxic potential in a lung cancer cell line (A549). The extraction of plant material was performed by using methanol (CME), followed by solvent-solvent partitioning with different solvents. The methanol (CME) and its subsequent fractions (pet-ether PEF, chloroform CHF, ethyl acetate EAF and aqueous AQF fractions) confirmed the presence of alkaloids, flavonoids, phenols, tannins and terpenoids at different degrees. The phenolic and flavonoid content were found to be 69.46, 37.93, 64.61, 126.74 and 60.64 mg of GAE/gm and 33.93, 4.11, 45.68, 146.95, and 44.36 mg of CAE/gm of dried CME, PEF, CHF, EAF and AQF, respectively. The overall antioxidant and iron reduction capacities of CME and all the fractions were in the following order: EAF > CHF > CME > AQF > PEF and EAF > CHF > CME > AQF > PEF, respectively. Among the fractions, EAF significantly scavenged DPPH (IC50 of 1.34 μg/ml) and OH radicals (IC50 of 4.38 μg/ml), which closely resembled those of standard BHT (IC50 of 0.9 μg/ml) and CA (IC50 of 2.73 μg/ml), respectively. Moreover, EAF (IC50 of 14.06 μg/ml) demonstrated a similar effect on inhibiting lipid peroxidation when compared to standard CA (IC50 of 13.86 μg/ml). In addition, CHF (24.25%) and EAF (14.9%) showed a potent cytotoxic effect in A549 cells. Our results suggest that P. lanceolata might be a good source of anticancer potential having antioxidant activity.Bangladesh Pharmaceutical Journal 27(2): 137-148, 2024 (July)